Genetic and antibiotic resistance profiles of thermophilic Campylobacter spp. isolated from quails (Coturnix coturnix japonica) in a Portuguese slaughterhouse. (January 2016) - Fraqueza, M.J.; Ribeiro, S.A.; Pereira, S.C.; Fernandes, M.H.; Fernandes, M.J.; Barreto, A.S.
Abstract: The aim of our study was to evaluate thermophilic Campylobacter frequency in quails at slaughterhouse level in two subsequent years. Campylobacter isolates were evaluated for their antibiotics resistance ability, looking for multidrug resistance. Their genetic diversity assessment was performed by pulsed field gel electrophoresis (PFGE) in order to establish possible relationships among different flocks and producers. This study highlights the high frequency (81–94%) and antimicrobial resistance of Campylobacter spp. in commercial quails. Campylobacter coli were dominant with a high frequency of resistance for fluoroquinolones, tetracycline and ampicillin among all the quail flocks and producers. C. coli strains with the same genetic profile isolated in samples from different flocks and producers, and collected in different slaughtering days, suggest the existence of common risk factors at production level in a vertically integrated enterprise. Strains' low genetic diversity with the prevalence of a single pulsotype among producers, might suggest that quails have been submitted continuously to the same therapeutics, which induced selectivity due to antibiotic stress pressure. C. coli contaminated quails might act as a source that increases consumer's exposure to multidrug-resistant isolates. Highlights: There is a high frequency (81–94%) of Campylobacter spp. in commercial quails. C. coli were frequently resistant to fluoroquinolones, tetracycline and ampicillin. Same pulsotype strains among producers suggest selectivity due to antibiotic use. Quails might act as a source of multidrug-resistant C. coli to consumers.